Characterization of software-defined radio implementation of a vector network analysis system - Ambatali, Charleston Dale M.
Software Defined Radios (SDR) are radios that are composed of RF front end and digital backend which is separated by a high speed analog to digital converter. The RF front end is capable of operating in a large range of frequencies and its bandwidth is tunable. The digital backend is composed of a digital signal processor and an operating system for user interface which enables the platform to be programmed by a user for a specific application. This reconfigurability enables the same platform to shift to different communication standards. With its digital processing backend and reconfigurable front end, an SDR is a suitable test and measurement instrument in the field of RF Engineering and Wireless Communications. Measurements in RF Engineering and Wireless Communications can be classified into three categories: signal analysis, spectrum analysis, and network analysis. Signal analysis and spectrum analysis requires minimal hardware and some signal processing power to implement a Fast Fourier Transform (FFT), which are already implemented in common SDRs. On the other hand, network analysis is not straightforward since it requires a number of RF front-end resources which adds errors to the measurement and post-processing is needed to de-embed these errors in the measurement. An example of an instrument which measures network parameters is the vector network analyzer (VNA). The common architecture used for VNAs require a single transmitter, three receivers, two couplers, one power splitter, and a digitally-controlled switch. Post-processing include the ability of the software to add and multiply matrices of complex numbers which is possible on an SDR. In terms of hardware, however, there is a challenge in implementing network analysis as SDRs in the market does not necessarily have enough transmit and receive ports to function as a VNA. To address this problem, a novel architecture is proposed to make efficient use of a common 2x2 Multiple Input Multiple Output (MIMO) SDR front-end resources with a corresponding calibration algorithm. It is shown through simulation that the proposed architecture and calibration algorithm is feasible in deem bedding the errors present in the setup. Comparing it with a commercial VNA, the error floor of the SDR-VNA is significantly higher and this can be attributed to the non-idealities in the architecture.